Systemic failures in New Zealand's child-welfare and Family Court proceedings underlie and perpetuate child offending - Reil, Jerome (Journal of criminology, 2025)
Early childhood offending onset (before age 14 years) is associated with increased risk of lifecourse offending and poor life outcomes. The vast majority of children who offend in Aotearoa New Zealand (N.Z.) have had involvement with the child-welfare system prior to offending. Why does this engagement with statutory systems not prevent the trajectory into offending, nor its persistence into the youth-justice system (aged 14–18)? This study interviewed 33 key stakeholders (including family members, lawyers, police officers, social workers, psychologists, school and cultural leaders) on the systemic issues they had experienced with children who had offended and their families. Interviews were transcribed and analysed by the authors. Barriers to effectively responding to offending (and, more importantly, prevention of offending in the first place) included child-welfare engagement that was delayed and ineffective; deficit-focused engagement with families and children; under-resourced Family Court systems that delayed court proceedings and further hindered effective child-welfare intervention; and systemic shortfalls that continued once a child had offended, with widespread uncertainty as to how best to respond or access appropriate resources. Earlier and more effective intervention with children and families with child-welfare concerns is needed to prevent and reduce offending and victimisation of and by children.